Genipin cross-linked gelatin hydrogel for encapsulating wharton jelly mesenchymal stem cells and basic fibroblast growth factor delivery in vocal fold regeneration - Wan-Chiew, Ng; Baki, Marina Mat; Lokanathan, Yogeswaran; Fauzi, Mohd Busra; Azman, Mawaddah (Frontiers in Cell and Developmental Biology, 2024)
Approaches to regenerate vocal fold in glottic insufficiency remains to be a focus for exploration. This is attributed to the applications of cells or biological molecules alone result in fast degradation and inadequate for regeneration. Development of an injectable hydrogel for glottic insufficiency is challenging, as it needs to be non-cytotoxic, elastic yet possess good strength and easy to fabricate. This gap prompts us to study the feasibility of our genipin(gn)-crosslinked gelatin (G) hydrogel in encapsulating Wharton’s Jelly Mesenchymal Stem Cells (WJMSCs) and basic fibroblast growth factor (bFGF) WJMSCs with the aim to provide regeneration in glottic insufficiency. WJMSCs was encapsulated into two optimised formulations with the density of 2,000,000 cells/mL. The encapsulated cells were tested for its morphology, cell viability, proliferation and migration. Then, the incorporation of basic fibroblast growth factor (bFGF) was done into a final formulation and was tested for the cellular response and in vitro inflammation. 6G 0.4gn demonstrated better cell viability after in vitro culturing for 7 day. After incorporation of bFGF into cell-laden 6G 0.4gn, encapsulated WJMSCs showed to have improved viability and migration. The inflammatory profile of the hydrogel was imperceptible and was regarded as minimal or no pro- and anti-inflammation. Altogether, we have first formulated 6G 0.4gn which is suitable to encapsulate WJMSCs and incorporation of bFGF. Current study fulfils the market need in vocal fold regeneration, by suggesting its rejuvenating potential in glottic insufficiency, yet this combined formulation should be studied further to justify its translation to clinical setting.